2005
DOI: 10.1124/jpet.105.091181
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Novel Allelic Variants of CYP2C9 Recently Discovered in Southeast Asians

Abstract: CYP2C9 was recently resequenced in 150 Asian subjects from Singapore. Several new coding variants were reported, and these variants are now named

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 32 publications
5
63
1
Order By: Relevance
“…Thus, the reason for the CYP2C9*13-mediated reduction in drug-metabolizing capability is unclear. CYP2C9*14, CYP2C9*16, and CYP2C9*19 were found in Southeast Asians and reported to exhibit moderately or markedly decreased intrinsic clearance of tolbutamide in vitro (DeLozier et al, 2005). In our study, only CYP2C9*19 markedly decreased the intrinsic clearance of BOS (1.65%) and caused a lower V max value (2.1%) relative to wild type, consistent with previous observations.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, the reason for the CYP2C9*13-mediated reduction in drug-metabolizing capability is unclear. CYP2C9*14, CYP2C9*16, and CYP2C9*19 were found in Southeast Asians and reported to exhibit moderately or markedly decreased intrinsic clearance of tolbutamide in vitro (DeLozier et al, 2005). In our study, only CYP2C9*19 markedly decreased the intrinsic clearance of BOS (1.65%) and caused a lower V max value (2.1%) relative to wild type, consistent with previous observations.…”
Section: Discussionsupporting
confidence: 82%
“…This allele was first identified in an Indian patient, and the variant protein exhibited 80-90% lower catalytic activity toward tolbutamide (7,8). CYP2C9*27 (Arg150Leu) and *30 (Ala477Thr), both detected recently in a Japanese population (11), were also identified in 3 and 2 individuals in the present study, respectively.…”
Section: Discussionsupporting
confidence: 71%
“…Arg133, the corresponding residue of CYP2B4, is suggested to play a prominent role in binding its redox partners, cytochrome b5 and P450 reductase (38). Accordingly, the loss of catalytic activity of the Arg132Gln variant might reflect the altered affinity of variant protein to these redox partners due to electrostatic changes as proposed for *2 (Arg144Cys), *14 (Arg125His), and *26 (Thr130Arg) (8,11,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP2C9*16(T299A) and CYP2C9*19(Q454H) were discovered after studying 125 Asians from Singapore (Zhao et al, 2004). In vitro study showed that CYP2C9*16 exhibited 80-90% lower catalytic activity of tolbutamide, whereas CYP2C9*19 exhibited 30-40% lower catalytic activity of tolbutamide, when compared with wild-type CYP2C9*1, CYP2C9*27, and CYP2C9*29 discovered in 263 Japanese individuals (DeLozier et al, 2005). Michaelis-Menten curves for diclofenac 4-hydroxylation from recombinant microsomes showed the identical Km and Vmax values of CYP2C9*27and CYP2C9*29 compared with the wild-type (Maekawa et al, 2006).…”
Section: Introductionmentioning
confidence: 99%